Effect of weaning and cow-calf contact on the physiological and clinical health, performance, and behaviour of dairy cows and their calves - S.E. McPherson; E.A.M. Bokkers; A.M. Sinnott; M.C. McFadden; L.E. Webb; E. Kennedy (Animal)
Cow-calf contact (CCC) systems have become increasingly popular calf−rearing systems to promote positive welfare; however, weaning and separation may cause distress. This preliminary study aimed to investigate the interaction between weaning and CCC on the physiological health, performance, and behaviour of dairy cows and calves. Three systems were compared: conventional, pasture-based Irish system (CONV; 18 pairs), cow and calf separated ≤ 2 h postbirth, cows milked twice-a-day, calves artificially reared indoors; full-time access system (FT; 14 pairs), dam and calf allowed constant, pasture-based, unrestricted access and cows milked twice-a-day; and part-time access system (PT; 18 pairs), unrestricted access at night indoors, cows grazed outdoors by day while calves remained indoors, cows milked once-a-day (0800 h). All calves were weaned at 8 weeks of age; FT and PT pairs underwent a 7 d gradual weaning and separation process (PT cows switched to twice-a-day milking) while CONV calves were gradually weaned over 12 d. Clinical health scores (2x/week), blood samples (1x/week; analysed for physiological markers of health and performance), BW (1x/week), body condition score (1x/week; cows only), and behaviour (1 d/week; scan sampling 3x/d; 24 total observations) were taken the week before (preWS) and after (postWS) the weaning and separation process. The PT cows had higher body condition scores (3.18 ± 0.034) than CONV (2.95; FT cows were similar to both, 3.05) and lower non-esterified fatty acids (NEFA; 0.40 ± 0.038 mmol/L) than the FT cows (0.58 mmol/L; CONV cows were similar to both, 0.48 mmol/L) across both time-points. All calves preWS had lower summed clinical health scores (0.91 vs 1.25 ± 0.131; P = 0.017), beta-hydroxybutyrate (0.07 vs 0.39 ± 0.023 mmol/L; P < 0.001), and globulin (12.0 vs 14.5 ± 0.929 g/L; P = 0.010) than postWS. After weaning and separation, the FT (0.36 mmol/L; P < 0.001) and PT (0.34 mmol/L; P = 0.001) calves had higher NEFA than CONV calves (0.13 mmol/L). Calf weekly average daily gain (ADGw) was similar preWS (0.9 ± 0.142 kg/d), but CONV calves had higher ADGw postWS than FT (0.42 kg/d) and PT calves (0.40 kg/d). All calves performed more (P = 0.009) positive behaviours preWS (4.6 ± 6.37%) compared to postWS (2.3 ± 3.38%). Our results suggest the applied CCC slightly worsened cow and calf health, performance, and behaviour around weaning and separation.